The Effect of E-Chemagz in the RADEC Model on Students Creativity and Learning Outcomes - Luthfiana, Luthfiana; Allo, Eda Lolo; Syahrir, Muhammad (Journal of The Indonesian Society of Integrated Chemistry, 2026)
This study aims to determine the effect of e-chemagz in the RADEC model on creativity and learning outcomes of 10th-grade students of State Senior High School 8 Makassar on the subject of chemical bonds. The method used is a quasi-experimental method with a posttest only control group design. The population in this study was all 10th-grade students of State Senior High School 8 Makassar. Random sampling was used to determine the research sample, and Class X Merdeka 1 was selected as the experimental class that used e-Chemagz in the RADEC model, while Class X Merdeka 2 was selected as the control class that did not use e-Chemagz in the RADEC model. Based on inferential analysis using the Mann Whitney test, it shows that student learning creativity obtained Zcount = 2.53 at (α) = 0.05 and obtained Ztable = 1.64, indicating that Zcount (2.53) > Ztable (1.64). while for learning outcomes, Zcount = 4.25 at (α) = 0.05 and Ztable= 1.64, indicating that Zcount (4.25) > Ztable (1.64). It can be concluded that E-Chemagz has an effect on the RADEC model in terms of creativity and learning outcomes of 10th-grade students of State Senior High School 8 Makassar on the subject of chemical bonding.